Direct PCR amplification of DNA from human bloodstains, saliva, and touch samples collected with microFLOQ® swabs. (January 2018) - Ambers, Angie; Wiley, Rachel; Novroski, Nicole; Budowle, Bruce
Highlights: Miniaturized microFLOQ ® swab used for direct amplification of DNA. microFLOQ ® subsamples a minute portion of a stain and preserves evidence. Consistently yielded higher STR peak heights than standard methods. Important implications for LCN and degraded samples that plague forensic casework. Abstract: Previous studies have shown that nylon flocked swabs outperform traditional fiber swabs in DNA recovery due to their innovative design and lack of internal absorbent core to entrap cellular materials. The microFLOQ ® Direct swab, a miniaturized version of the 4N6 FLOQSwab ®, has a small swab head that is treated with a lysing agent which allows for direct amplification and DNA profiling from sample collection to final result in less than two hours. Additionally, the microFLOQ ® system subsamples only a minute portion of a stain and preserves the vast majority of the sample for subsequent testing or re-analysis, if desired. The efficacy of direct amplification of DNA from dilute bloodstains, saliva stains, and touch samples was evaluated using microFLOQ ® Direct swabs and the GlobalFiler™ Express system. Comparisons were made to traditional methods to assess the robustness of this alternate workflow. Controlled studies with 1:19 and 1:99 dilutions of bloodstains and saliva stains consistently yielded higher STR peak heights than standard methods with 1 ng input DNA from the same samples. Touch samples from common items yielded single source and mixed profiles that were consistent with primary users of the objects. With this novel methodology/workflow, no sample loss occurs and therefore more template DNA is available during amplification. This approach may have important implications for analysis of low quantity and/or degraded samples that plague forensic casework.